Moderate physical activity from childhood contributes to metabolic health and reduces hepatic fat accumulation in adult rats - de Moura, Leandro Pereira (BioMed Central, 2013)
BACKGROUND: Obesity, oxidative stress and inflammation, by triggering insulin resistance, may contribute to the accumulation of hepatic fat, and this accumulation by lipotoxicity can lead the organ to fail. Because obesity is growing at an alarming rate and, worryingly, in a precocious way, the present study aimed to investigate the effects of moderate physical training performed from childhood to adulthood on liver fat metabolism in rats. METHODS: Twenty rats that were 28 days old were divided into two groups: control (C) and trained (T). The C Group was kept in cages without exercise, and the T group was submitted to swimming exercise for 1 hour/day, 5 days/week from 28 to 90 days of age (8 weeks) at 80% of the anaerobic threshold determined by the lactate minimum test. At the end of the experiment, the body weight gain, insulin sensitivity (glucose disappearance rate during the insulin tolerance test), concentrations of free fatty acids (FFA) and triglycerides (TG) and hepatic lipogenic rate were analyzed. For the statistical analysis, the Student t-test was used with the level of significance preset at 5%. RESULTS: The T group showed lower body weight gain, FFA concentrations, fat accumulation, hepatic lipogenic rate and insulin resistance. CONCLUSION: The regular practice of moderate physical exercise from childhood can contribute to the reduction of obesity and insulin resistance and help prevent the development of accumulation of hepatic fat in adulthood.